Disseminated histiocytic sarcoma in a degu (Octodon degus) - IKEDA, Mitsuhiro; KONDO, Hirotaka; HAMADA, Fuyu; YAMASHITA, Tomoyuki; SHIBUYA, Hisashi (Journal of Veterinary Medical Science, 2024)
A 7-year-and-8-month-old, male degu (Octodon degus) with anorexia, depression, and labored breathing was found to have a thoracic effusion and enlargement of the right testis on radiographic examination. Despite treatment, the animal died. At necropsy, hepatomegaly, splenomegaly, and multifocal nodules on the intestinal serosa and mesentery were observed. Histologically, the foci were densely cellular invasive neoplasms composed of sheets of round to polygonal cells, with occasional multinucleated giant cells. Immunohistochemically, the neoplastic cells were immunopositive for ionized calcium-binding adapter molecule 1, human leukocyte antigen-DR, and CD204. These findings were consistent with disseminated histiocytic sarcoma.